Thermal-fluid dynamic study of a laboratory level prototype of a solar water heater that reuses plastic bottles - Alfaro Ayala, Jorge Arturo; Crespo Quintanilla, Jesús Alberto (Acta Universitaria, 2019)
This work presents an investigation of the performance of a solar water heater made of plastic bottles (recycled material). The study was carried out through numerical simulations with the computational fluid dynamics (CFD) and tests at a laboratory level prototype that reuses plastic bottles of polyethylene terephthalate (PET). Water is heated through the reception of the solar radiation on the surface of the PET bottle. The prototype was made of plastic filament called polylactic acid (PLA) using a 3D printing. The results showed that the solar water heater that reuses PET bottles reaches a maximum temperature of 315 K (42 ºC). The validation of the CFD numerical model was made with the experimental results, obtaining relative errors less than 1.69%. This work presents an investigation of the performance of a solar water heater made of plastic bottles (recycled material). The study was carried out through numerical simulations with the computational fluid dynamics (CFD) and tests at a laboratory level prototype that reuses plastic bottles of polyethylene terephthalate (PET). Water is heated through the reception of the solar radiation on the surface of the PET bottle. The prototype was made of plastic filament called polylactic acid (PLA) using a 3D printing. The results showed that the solar water heater that reuses PET bottles reaches a maximum temperature of 315 K (42 ºC). The validation of the CFD numerical model was made with the experimental results, obtaining relative errors less than 1.69%.